2019
DOI: 10.3748/wjg.v25.i30.4061
|View full text |Cite
|
Sign up to set email alerts
|

Issues and controversies in esophageal inlet patch

Abstract: The proximal esophagus is rarely examined, and its inspection is often inadequate. Optical chromoendoscopy techniques such as narrow band imaging improve the detection rate of inlet patches in the proximal esophagus, a region in which their prevalence is likely underestimated. Various studies have reported correlations between these esophageal marks with different issues such as Barrett’s esophagus, but these findings remain controversial. Conflicting reports complicate the process of interpreting the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 81 publications
1
15
0
1
Order By: Relevance
“…Akbayır et al also indicated that the rate of women was higher in their study (14). In a review by Ciocelteu et al, IP was more common in women and can appear as hypochondria when it is associated with anxiety (11). We found that the presence of more specific symptoms and the globus sensation were approximately 3 times higher in women then men (Table 1).…”
Section: Conflicts Ofsupporting
confidence: 59%
See 2 more Smart Citations
“…Akbayır et al also indicated that the rate of women was higher in their study (14). In a review by Ciocelteu et al, IP was more common in women and can appear as hypochondria when it is associated with anxiety (11). We found that the presence of more specific symptoms and the globus sensation were approximately 3 times higher in women then men (Table 1).…”
Section: Conflicts Ofsupporting
confidence: 59%
“…Interestingly, we did not find a significant relationship between IP size (p = 0.807) and IP numbers (p = 0.586) of 9 patients with globus sensation and 44 patients without it (Table 3). Ciocalteu et al also observed such a relationship (11).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…GH is largely asymptomatic and discovered incidentally. Some symptoms include heartburn, chronic cough and hoarseness, which may be attributed to the potential of inlet patches produce acid, but mucous production has also been implicated [ 9 , 10 ]. Complications of esophageal GH include laryngitis, esophagitis, esophageal web, stricture, ulcer, perforation and fistula [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…İP: İnlet patch, NBI: Dar band görüntüleme.ki darlık olabileceği düşünülmüştür(31,32). Yine literatürde İP'li hastalarda en sık semptomun boyuta bağlı korelasyonu olmayan globus hissi olduğu bildirilmiştir(22). Hori ve ark.…”
unclassified